Artificial Intelligence Control Applied in Wind Energy Conversion System - Arama Fatima Zohra; Bousserhane Ismail Khalil; Laribi Slimane; Sahli Youcef; Mazari Benyounes (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The objective of this paper is to study the dynamic response of the wind energy conversion system (WECS) based on the Doubly Fed Induction Generator (DFIG). The DFIG rotor is connected to the grid via a converter. The active and reactive power control is realized by the DFIG rotor variables control, using the field oriented control (FOC). The vector control of DFIG is applied by the use of tow regulators PI and the neural network regulator (NN). The generator mathematical model is implemented in Matlab/ Simulink software to simulate a DFIG of 1.5 MW in order to show the efficiency of the performances and robustness of the studied control systems. The simulation obtained results shows that the robustness and response time of the neural network regulator is better than those obtained by the PI classical regulator.